Influence of aspect ratio and surface defect density on hydrothermally grown ZnO nanorods towards amperometric glucose biosensing applications - Shukla M.; Pramila; Dixit T.; Prakash R.; Palani I.A.; Singh V. (My University, 2025)
In this work, hydrothermally grown ZnO Nanorods Array (ZNA) has been synthesized over Platinum (Pt) coated glass substrate, for biosensing applications. In-situ addition of strong oxidizing agent viz KMnO 4 during hydrothermal growth was found to have profound effect on the physical properties of ZNA. Glucose oxidase (GO x ) was later immobilized over ZNA by means of physical adsorption process. Further influence of varying aspect ratio, enzyme loading and surface defects on amperometric glucose biosensor has been analyzed. Significant variation in biosensor performance was observed by varying the amount of KMnO 4 addition during the growth. Moreover, investigations revealed that the suppression of surface defects and aspect ratio variation of the ZNA played key role towards the observed improvement in the biosensor performance, thereby significantly affecting the sensitivity and response time of the fabricated biosensor. Among different biosensors fabricated having varied aspect ratio and surface defect density of ZNA, the best electrode resulted into sensitivity and response time to be 18.7 mA cm −2  M −1 and <5 s respectively. The observed results revealed that apart from high aspect ratio nanostructures and the extent of enzyme loading, surface defect density also hold a key towards ZnO nanostructures based bio-sensing applications. © 2017 Elsevier B.V.